Influence of Heating Temperature on the Ink Transfer to Polymer Substrates in the Retransfer Printing Process - Hoang, Thi Kieu Nguyen (Journal of Technical Education Science, 2024)
This study explores the effect of heating temperature on the ink transfer to Poly(vinyl chloride) and Poly(ethylene terephthalate) substrates in a specific retransfer printer. A notable correlation between heating temperature and solid color density was observed. The color density increases with heating temperature until reaching a critical threshold, typically around 140°C. Beyond this threshold, color density begins to decline due to ink penetration into the substrate, reducing ink film thickness on the surface of the substrates. This critical temperature is predominantly influenced by the properties of the ink rather than the characteristics of the substrate. The experimental study also reveals that variations in temperature-dependent ink transfer lead to noticeable color differences compared to standard references. An optimal temperature range of 120°C to 140°C was established, within which the process colors conform to the ISO 12647 standard, achieving DE values below 5. These results highlight the importance of maintaining appropriate ink transfer conditions to ensure precise color reproduction in printing processes.